Crystal Structure Studies of Human Dental Apatite as a Function of Age - Leventouri, Th.; Antonakos, A.; Kyriacou, A.; Venturelli, R.; Liarokapis, E.; Perdikatsis, V. (International Journal of Biomaterials, 2009)
Studies of the average crystal structure properties of human dental apatite as a function of age in the range of 5–87 years are reported. The crystallinity of the dental hydroxyapatite decreases with the age. The a-lattice constant that is associated with the carbonate content in carbonate apatite decreases with age in a systematic way, whereas the c-lattice constant does not change significantly. Thermogravimetric measurements demonstrate an increase of the carbonate content with the age. FTIR spectroscopy reveals both B and A-type carbonate substitutions with the B-type greater than the A-type substitution by a factor up to ~5. An increase of the carbonate content as a function of age can be deduced from the ratio of the ν2CO3 to the ν1PO4 IR modes.